Visual acuity and progression of macular atrophy in patients receiving intravitreal anti-VEGF for age-related macular degeneration. Issue 1 (January 2022) - Ji, Marco H; Callaway, Natalia F; Ludwig, Cassie A; Vail, Daniel; Al-Moujahed, Ahmad; Rosenblatt, Tatiana R; Leng, Theodore; Sanislo, Steven R; Moshfeghi, Darius M
Purpose: Whether intravitreal anti-vascular endothelial growth factors (VEGFs) cause retinal atrophy is still a subject of debate. We reported 13 eyes that received several injections of anti-VEGF for wet age-related macular degeneration (AMD) with good visual acuity despite geographic atrophy on imaging. Methods: This is a case series study conducted at Byers Eye Institute at Stanford University. Patients of three retina specialists with wet AMD who received six or more intravitreal injection of anti-VEGFs with visual acuity of 20/60 or better and incomplete RPE and outer retina atrophy (iRORA) or complete RPE and outer retinal atrophy (cRORA) were enrolled in this case series. Different imaging modalities were reviewed by three retina specialists comparing the baseline with the most recent exam. Results: About 13 eyes of 10 patients met the selection criteria. Eleven eyes were classified as iRORA and 2 as cRORA. Despite the development of macular atrophy on imaging after an average of 38.1 injections, eyes maintained stable visual acuity. Conclusion: The discrepancy between structural and functional findings in this cohort suggests that patients treated by anti-VEGF drugs exhibit divergent clinical outcomes for currently unknown reasons. The authors propose anti-VEGF may affect melanosomes within RPE without disrupting RPE and photoreceptors function completely. This requires further investigation.